Transferência do tratamento diretamente observado da tuberculose na atenção básica de Santa Maria/RS e Uruguaiana/RS - Dambrós, Amanda Brutti (2023)
Introduction: Directly Observed Treatment in Brazil was implemented with the aim of reducing the rates of abandonment of tuberculosis treatment. However, in some municipalities such as Santa Maria/RS and Uruguaiana/RS, treatment is carried out centrally, contrary to what is recommended by the Ministry of Health. Objective: To analyze the transfer of the Directly Observed Treatment policy for tuberculosis according to Primary Care professionals, physicians, nurses and nursing technicians in Santa Maria/RS and Uruguaiana/RS. Method: It is a quantitative, descriptive and transversal work. Data collection took place from February to March 2022 in Uruguaiana/RS and August to November 2022 in Santa Maria/RS. The instrument used was an adapted “Policy Transfer Assessment: Innovation, Information and Knowledge on Tuberculosis”. Data analysis was performed using the SPSS program, using techniques such as simple and cumulative frequency, mean, mode, median and standard deviation, depending on the characteristics of the variables. Data reliability was tested using Cronbach's alpha and then data normality was analyzed. Results and discussion: 123 professionals participated in the study. From the analysis of the 20 items that make up the scale, it was possible to identify that 15 (75%) were evaluated as unfavorable for transferring the Directly Observed Treatment of tuberculosis, with aspects that do not contribute to the transfer process (considering the point cutoff=1.0-3.9), these items were related to management actions, professional knowledge about this policy, presence of human resources and popular participation in discussions on the topic. Only five (15%) were considered favorable for the transfer process (cutoff point=4.0-5.0), these items dealt with the incorporation of sectors other than health in the planning of actions aimed at tuberculosis, flexibility of the unit of health in releasing the professional for training and qualification and recognition of the importance of the theme. It was observed that the study participants have knowledge about the importance of Directly Observed Treatment, but have few opportunities for training on the subject. Conclusion: The need to invest in permanent and continuing education actions is reinforced, in order to qualify the assistance aimed at people with tuberculosis, promoting disease control, in addition to increasing adherence to treatment and, consequently, the cure.